Ultrastructural and proliferative features of the ventral lobe of the prostate in non-obese diabetic mice (NOD) following androgen and estrogen replacement associated to insulin therapy - Favaro, W. J.; Padovani, C. R. [UNESP]; Cagnon, V. H. A. (Churchill Livingstone, 2009)
Diabetes causes harmful effects on prostatic function. Thus, the aims of this study were to characterize morphological and proliferative features of the prostate of diabetic mice after long-term glycemic control and testosterone and estrogen replacement. A total of 48 mice (Nod and BALBc) were used. After 20 days in a diabetic state, the mice were divided into six groups: the control group received a 5 mL/kg dose of peanut oil; the diabetic group received the same treatment as the control group; the diabetic-insulin group received 4 IU doses of insulin; the diabetic-testosterone group received a 5 mg/kg dose of testosterone cypionate; the diabetic-estrogen group received a 25 mu g/kg dose of 17 beta-estradiol: the diabetic-insulin-testosterone-estrogen group received insulin, testosterone and estrogen at the same concentration as the other groups. After 20 days, the ventral lobe was processed for morphological and immunological analyses. The results showed structural disorganization, which was more intense in the diabetic group than in the other groups. The diabetic state showed a proliferation and apoptosis rate that was two times higher than that found in the control group. To conclude, diabetes disturbed the prostatic secretory activity and the association of insulin, testosterone and estrogen was crucial for glandular structural restoration, characterizing the complex activity of the prostate. The imbalance verified between the proliferation process and apoptosis in diabetic mice showed diabetes to be a triggering factor for prostatic pathogenesis. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Ventral prostate; Diabetes mellitus; Ultrastructural; Steroid hormones; Apoptosis; Proliferation